Dark Chocolate: Opportunity for an Alliance between Medical Science and the Food Industry? - Petyaev, Ivan M.; Bashmakov, Yuriy K. (Frontiers in Nutrition, 2017)
ABSTRACT Dark chocolate (DC) was originally introduced in human nutrition as a medicinal product consumable in a liquid form. Century-long efforts of food industry transformed this hardly appealing product into a valuable modern culinary delight with clear predominance of confectionery brands of DC on the market. However current epidemiological data as well as multiple experimental and clinical observations reveal that DC consumption may have a profound effect on cardiovascular, central nervous systems, hemostasis and lipid metabolism. However, despite of growing body of modern scientific evidence revealing medicinal properties of cocoa-based products, dark chocolate (DC) remains more gourmet culinary item than medicinal food product. Even today there are no clear dietary recommendations on consumption of cocoa flavonoids (flavanols) for health purpose. Clinical trials with DC rarely include monitoring of plasma flavanol concentration in volunteers. Moreover, there is no standardized assay or any quantitative requirements for flavanol content in the commercial brands of DC. High flavanol content is often sacrificed during manufacturing for a better taste of DC due to bitterness of cocoa flavonoids. All these problems including subsequently arising ethical issues need to be addressed by joint efforts of food industry and medical science. Moreover, application of microencapsulation technology in DC manufacturing, as well as molecular selection of best flavanol producers may drastically change bioavailability of DC bioactive ingredients and DC production technology. Nevertheless, only strict causative approach linking possible health effect of DC to its bioactive ingredients considered as nutraceuticals, may change the current landscape in nutritional research related to cocoa-based products and create a trustworthy path for their medicinal use.